DIVERSITY OF INVASIVE ANT SPECIES IN THE DUSUNG AGROFORESTRY AREA OF URENG VILLAGE - Nureny Goo, Fransina Latumahina, Betty Sahetapy (International Journal of Advanced Science and Technology, 2020)
The research was carried out in the dusung area of ​​the Ureng village in Central Maluku Regency to find out the spread of invasive ants in June - August 2018. The study used a survey method on 10 observation lanes measuring 100 x 10 m with a distance between 10 m lanes. Ant sampling used intensive collection techniques in some ant habitats, namely (1) in litter or soil, (2) above ground level, and (3) in plants (vegetation) with a range of time between 15-30 minutes. In one plot, the researcher only collected a few individuals that are similar species, so the species richness data obtained was presence-absence data. Ants were collected in microtubes containing 70% alcohol and labeled and identified to species level using the Guide Identification Guide to The Ant Genera of The World. The results found 8 types of invasive ants namely Anopolepis gracilipes, Leptogenys diminuta, Monomorium destructor, Odontoponera denticulate, Paratrechina longicornis, Soleonopsis geminate, Tapinoma melanocephalum, Technomyrmex albipes. The presence of 8 types of invasive ants adversely affects the lives of other insects and native ants in the dusung ecosystem in Ureng Village. The ants of A. gracilipes dominated the dusung area of ​​2920 individuals, the relative abundance of 45.7% and species diversity of 3.19, which was classified as high. The results of the correlation analysis show that environmental factors correlate with species diversity, species richness and species dominance in general. The species richness of vegetation was highly correlated with ant diversity (r = 1, p = 0,000, R2 = 0.717) and ant dominance (r = -1,000, p = 0,000 and R2 = 0.650). Vegetation diversity was significantly correlated with ant diversity (r = -0,900, p = 0.019, R2 = 0.926), ant species richness (r = 0.900, p = 0.900, R2 = 0.784) and ant dominance (r = -0.900, p = 0.019 , R2 = 0.856).